Wayfaring stranger : a novel - Burke, James Lee, 1936- (Simon & Schuster, 2014)
"WAYFARING STRANGER begins in West Texas in 1934. At age sixteen, Weldon Holland encounters Clyde Barrow and Bonnie Parker traveling with their accomplices after having just pulled off one of their notorious armed robberies. Weldon is smitten by Bonnie, but because of Clyde and Bonnie's duplicity and the disrespect they show his grandfather, Weldon ends up putting a bullet through the rear window of Clyde's stolen automobile. The story then jumps to 1944 and the Ardennes Forest and the Battle of the Bulge, where Second Lieutenant Weldon Holland saves his sergeant, Hershel Pine, from death by suffocation when he is buried alive in his foxhole under the treads of a Waffen SS Tiger tank. Weldon and Hershel survive the executions of the wounded by the SS and escape on a freight train deep into Nazi Germany. There, they stumble into an extermination camp deserted by the SS, and discover among the stacked bodies a young woman named Rosita Lowenstein, who is not only a remarkable woman but a relative of Rosa Luxemburg (known as "Red Rosa," whose mother's name was Lowenstein). Eventually, Weldon will make her his bride, and the three friends will return to Texas to seek their fortunes. But when Weldon, Hershel, and Rosita form a pipeline corporation, they enter the domain of jackals known as the oil business. They meet Roy Wiseheart--one of the wealthiest men in Texas and a former Marine aviator haunted with guilt for deserting his squadron leader over the South Pacific--and Roy's wife Clara, a vicious anti-semite who is determined to make Weldon and Rosita's life a nightmare"--